PENGARUH PENDIDIKAN KESEHATAN TERHADAP PERSEPSI REMAJA PUTRI TENTANG PERNIKAHAN DINI DI MTS HADANA DARUSSALAM KABUPATEN KAMPAR - Nurhayere Nurhayere; Rifa Yanti; Fajar Sari Tanberika; Rika Ruspita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Early marriage remains a public health issue affecting adolescents' reproductive health, psychological well-being, and socio-economic status. This study aimed to determine the effect of health education on young girls’ perceptions of early marriage at MTS Hadana Darussalam, Kampar Regency. A pre-experimental design with a one-group pretest-posttest approach was applied. The study was conducted in July–August 2025 at MTS Hadana Darussalam. The population consisted of 46 female students, and 32 respondents were selected using simple random sampling based on inclusion criteria. Primary data were collected through a perception questionnaire, while secondary data came from school records. Data collection included a pretest, health education using leaflets, and a posttest. Data analysis used univariate and bivariate methods with a dependent t-test at a significance level of 0.05. The results showed a significant increase in positive perceptions after receiving health education (p=0.000), indicating that health education effectively influenced young girls’ perceptions of early marriage. It is recommended that schools and health workers conduct regular health education to prevent early marriage. Keywords: Health Education, Perception, Early Marriage, Adolescent Girls